EFFECT SUBSTITUTION OF CASSAVA LEAF MEAL (Manihot Utilisima) FERMENTATION Rhizopus sp. ON FEED TO GROWTH AND SURVIVAL RATE Cyprinus carpio SEEDS - Rahmadani, Sri; Setyowati, Dewi Nur’aeni; Lestari, Dewi Putri (Jurnal Perikanan Unram, 2020)
This study aims to determine the growth and survival rate Cyprinus carpio seeds fed fermented cassava leaf flour using Rhizopus sp. The method used in this study was an experimental method using a Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications to obtain 15 experimental units, namely P0 (without the addition of fermented cassava leaf meal), P1 (addition of 10% fermented cassava leaf meal), P2 (addition of 15% fermented cassava leaf meal), P3 (addition of 20% fermented cassava leaf meal), and P4 (addition of 25% fermented cassava leaf meal. The results showed that there was no significant effect on absolute growth, daily growth rate, Feed Conversion Ratio (FCR), and Survival rate of carp. It is known that P1 (addition of 10% fermented cassava leaf meal) is the best treatment for all test parameters. As for the survival rate of P3 (addition of 20% fermented cassava leaf meal) and P4 (addition of 25% fermented cassava leaf meal) is the best treatment for survival that is 100%.